Physical and chemical characteristics in peat lands of Aceh Jaya District, Indonesia. Issue 1 (June 2020) - Arabia, T; Basri, H; Manfarizah; Zainabun; Mukhtaruddin
Abstract: This study aims to determine the physical and chemical characteristics of the peat lands (Histosols) in Aceh Jaya District using descriptive method. The results showed that some physical characteristics such as: water saturation in drilling-M1 (fibric soil materials) was 786.06% higher than drilling-M2 (hemic soil materials) and drilling-M3 (sapric soil materials) were 568.01% and 549.97%, respectively. Bulk density (BD) of drilling-M1, drilling-M2 and drilling-M3 are very low (0.08 - 0.12 g cm −3 ). Porosity in drilling-M1, drilling-M2 and drilling- M3 are classified as very porous at 95.00%, 93.00% and 90.54%. Some chemical characteristics show as follows: pH in drilling-M1, drilling-M2, and drilling-M3 categorized acid (4.52 - 5.16). Organic-C in drilling-M1, drilling-M2, and drilling-M3 ranges of 20.75 - 55.62% (very high). Exchangeable bases for calcium (3.6 - 23.9 cmol.kg −1 ), Mg (0.6 - 18.1 cmol.kg −1 ), and K (0.18 - 1.22 cmol.kg −1 ) are classified as low - very high. Exchangeable acidity for H (1.2 - 6.1 cmol.kg −1 ) higher than Al measured only in the drilling of M3 layers of Oa3 (2.3 cmol.kg −1 ). The CEC in drilling-M1, drilling-M2 and drilling-M3 ranges from 35.28 - 204.48 cmol.kg −1 (high - very high). Bases saturation (BS) ranges from very low - high (11.73 - 73.27%). Soil EC ranges 0.48 - 0.92 dS cm −1 (very low).